2013
DOI: 10.3171/2013.5.spine12473
|View full text |Cite
|
Sign up to set email alerts
|

Association between low-back pain and lumbar spine bone density: a population-based cross-sectional study

Abstract: Object The authors undertook this study to investigate the relationships between low-back pain (LBP) and spinal bone density. Low-back pain is a major health issue and contributes to increases in medical and economic costs. Epidemiological studies have identified individual, sociodemographic, psychosocial, and occupational risk factors for LBP. However, there have been limited studies addressing the relationships between LBP and spinal bone density. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
(41 reference statements)
2
8
1
Order By: Relevance
“…This study was based on a large, representative Korean population with data obtained from a well-established national cohort [38]. The prevalence of LBP in this study was comparable with previous studies [6][7][8][9]45]. Risk prediction equations based on general medical practice data are easily implemented in medical practice [46], and we believe our results are applicable to the general Korean popula-Mukasa and Sung tion.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This study was based on a large, representative Korean population with data obtained from a well-established national cohort [38]. The prevalence of LBP in this study was comparable with previous studies [6][7][8][9]45]. Risk prediction equations based on general medical practice data are easily implemented in medical practice [46], and we believe our results are applicable to the general Korean popula-Mukasa and Sung tion.…”
Section: Discussionsupporting
confidence: 80%
“…The annual and point prevalence of LBP approximates 45% and 30%, respectively [6]. Lee et al [7] reported a 17.1% total prevalence of LBP in Korea, whereas among hypertensive individuals, lifetime prevalence was 34.4% [8]. The reported prevalence of LBP varies substantially depending on the case definition used [9].…”
Section: Original Articlementioning
confidence: 99%
“…Although a previous study in the general population reported that the incidence of LBP increased with age [21], the selected two associating factors were independent of age in this study. The reason why age was not a significant predictor in the current study may be the difference in lumbar alignment between patients with hip OA and the general population.…”
Section: Relationship Between Low Back Pain and Confounding Factorscontrasting
confidence: 57%
“…To The ediTor: We read with great interest the article of Lee et al 2 (Lee S, Nam CM, Yoon DH, et al: Association between low-back pain and lumbar spine bone density: a population-based cross-sectional study. Clinical article.…”
Section: Degenerative Disc Disease and Osteoporosismentioning
confidence: 99%